Intervensi Cognitive Behavioral Therapy Terhadap Penurunan Tingkat Cemas Pada Pasien Systemic Lupus Erythematosus: A Systematic Review - Setiawan, Arief Dwi; Waluyo, Agung (Jurnal Ners, 2024)
Apart from affecting various body systems, Systemic Lupus Erythematosus (SLE) also has a psychological impact on sufferers, where most people report experiencing symptoms related to anxiety. Anxious complaints in SLE patients are associated with higher disease activity and an increase in body system disorders. Exposure to and experience of life-threatening events also contributes to anxiety in SLE patients. Psychotherapy interventions such as Cognitive Behavioral Therapy (CBT) can help reduce anxiety and improve quality of life. Objective: to provide an overview of whether Cognitive Behavioral Therapy intervention is effective in reducing anxiety levels in Systemic Lupus Erythematosus patients. Method: writing this article used a systematic review carried out through a search strategy in 6 databases, namely ProQuest, Springer Link, ScienceDirect, Sage Journal, Scopus, and Taylor & Francis with a total of 3,571 articles obtained. These articles were then filtered based on inclusion and exclusion criteria, leaving 10 articles. A total of 10 articles that met the criteria were then subjected to critical appraisal using the JBI Critical Appraisal Checklist guidelines. Results: In general, this systematic review shows that CBT intervention can effectively reduce anxiety levels in SLE patients.